Microbiological quality and safety of commercial fresh fruit and vegetable juices in Korea. (December 2021) - Lee, Soyul; Han, Areum; Jo, Suyoung; Cheon, Hyewon; Song, Hana; Jang, A-Ra; Kim, Danbi; Lee, Sun-Young
Abstract: Fresh fruit and vegetable juices that have not been pasteurized can cause foodborne diseases. Therefore, microbial quality monitoring of fresh fruit and vegetable juices sold domestically is necessary. Here, 100 fresh fruit and vegetable juices were purchased from online and offline stores in Korea and monitored quantitatively and qualitatively for general microbial quality and foodborne pathogens. Total aerobic bacteria (TAB), coliform, yeast/mold (Y/M), Bacillus cereus, Staphylococcus aureus, Escherichia coli O157:H7, Listeria monocytogenes, and Salmonella spp. were evaluated by the selective agar method. TAB were detected in 51 out of 100 samples at an average level of 4.21 ± 1.10 log CFU/mL, and coliform and Y/M were detected in 39 and 52 samples at average levels of 3.24 ± 1.13 and 3.47 ± 1.12 log CFU/mL, respectively . E. coli O157:H7, L. monocytogenes, and Salmonella spp. were not detected in any of the tested samples, but B. cereus and S. aureus were detected in 12 and 1 samples, respectively. This study can be used as basic data for technology development to secure the microbial quality and safety of fresh fruit and vegetable juices. Highlights: The microbiological quality of fresh fruit and vegetable juices sold in Korea was evaluated. The microbiological quality of juices containing vegetable or juices without sterilization and HACCP processing was poor. All juices in which Bacillus cereus was detected were juices containing one or more vegetables. Juices containing vegetables as ingredients require a separate process for microbiological quality control.